Penerapan Fungsi MSDM Dalam Meningkatkan Tugas Polisi Khusus Pemasyarakatan Di Lapas Kelas I Kota Makassar - Alfin, Alfin; Mahsyar, Abdul; Usman, Jaelan (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2020)
This study aimed to find out how the application of the HRM function in improving the special police duties in Class 1 Prison Makassar City. This study used qualitative descriptive research. The number of informants in this study was 5 people. Data analysis techniques were carried out qualitatively. The results of the study showed that the application of the HRM function in improving the special police officers'  in Class 1 Prison in Makassar City had been oriented to improve the tasks or competence of the National Police Station in developing the inmates who were already competent and in line with the tasks and training that had been received by the police station staff, then applied it directly in his task of fostering prisoners, with the aimed was prisoners could be useful in the community and no longer commit crime. But in the case of oversight carried out by the police station  was not optimal, because there were still violations, namely the smuggling of cell phones that recently occurred in the last few months. Supervision should be carried out more stringently and monitored every 2 times 24 hours so that  no more suppliers broughtbelectronic for prisoners.